M. G. Krein’s ideas in the theory of orthogonal polynomials - Osilenker, B. P. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We present a survey of M. G. Krein’s ideas in tho theory of orthogonal polynomials.